2017
DOI: 10.1016/j.jacl.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

ABCG5/G8 gene is associated with hypercholesterolemias without mutation in candidate genes and noncholesterol sterols

Abstract: Mutation-negative FH subjects accumulate an excess of rare and common gene variations in ABCG5/G8 genes. This variation is associated with increased intestinal absorption of cholesterol, as determined by surrogate makers, suggesting that these loci contribute to hypercholesterolemia by enhancing intestinal cholesterol absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 30 publications
2
24
0
1
Order By: Relevance
“…We found that additional mutation(s) in the ABCG5/8 genes significantly affected LDL cholesterol level and coronary artery disease prevalence. These findings and a recent study revealed that ABCG5/8 genetic mutations significantly affected LDL cholesterol levels in the general population; this information supports the notion that there are many heterozygous carriers of this disease among patients with hypercholesterolemia 13 ) . The mutations that could cause sitosterolemia and polymorphisms are illustrated in Fig.…”
Section: Abcg5 and Abcg8 Mutationssupporting
confidence: 83%
“…We found that additional mutation(s) in the ABCG5/8 genes significantly affected LDL cholesterol level and coronary artery disease prevalence. These findings and a recent study revealed that ABCG5/8 genetic mutations significantly affected LDL cholesterol levels in the general population; this information supports the notion that there are many heterozygous carriers of this disease among patients with hypercholesterolemia 13 ) . The mutations that could cause sitosterolemia and polymorphisms are illustrated in Fig.…”
Section: Abcg5 and Abcg8 Mutationssupporting
confidence: 83%
“…On the other hand, a growing body of evidence suggests that rare and deleterious mutations in ABCG5/ABCG8 contribute to the development of the FH phenotype, especially among FH mutationnegative patients. [4][5][6] We previously showed that concomitant mutations in "accessory" genes, including ABCG5 and criteria specified by the Japan Atherosclerosis Society: (1) LDL-C ≥180 mg/dL, (2) tendon xanthoma (tendon xanthoma on the backs of hands, elbows, knees, etc. or Achilles tendon hypertrophy; X-ray assessed Achilles tendon thickness ≥9 mm) or xanthoma tuberosum, and (3) family history of FH or premature CAD among the patient's 2nd-degree relatives.…”
mentioning
confidence: 99%
“…Variants of ABCG5/8 are associated with sitosterolemia and higher levels of total cholesterol and triglycerides as well as lower levels of HDL-C [87] Mutation-negative patients with FH Sanger sequencing [92] Case report of FH Targeted NGS [107] Case/control study of patients with FH TaqMan genotyping [91,93,108] Case/control study of patients with FH Meta-analysis [108] PNPLA5 Individuals with extremely high and extremely low LDL-C from population-based cohorts Whole-exome sequencing Variants of PNPLA5 are associated with extremely high LDL-C levels [104] In 2019, Luis Masana and co-workers proposed a new classification of FH on behalf of the Expert Group of the Spanish Arteriosclerosis Society ( Table 2). The factors that prompted the creation of the new classification were 1) discrepancies between the clinical and genetic diagnosis of FH, when FH-associated mutations are not found in people with the clinical diagnosis of definite FH; 2) variation in the clinical signs of FH; 3) high risk of vascular complications among patients with monogenic or polygenic FH; and 4) treatment of FH confirmed by molecular genetic methods with new classes of drugs [111].…”
Section: Discussionmentioning
confidence: 99%
“…Among patients with FH, carriers of the Gln604Glu allele (rs6720173) of ABCG5 are reported to have a lower concentration of triglycerides and very-low-density lipoprotein, whereas the presence of intron variant rs4131229A>G, rs4148189C>T, or rs4289236G>A of this gene has been found to be associated with higher levels of total cholesterol and triglycerides as well as a lower level of HDL-C only in smokers [91]. In Spanish patients with hypercholesterolemia, Asn578Ser (rs146534033), Gly288Cys (rs139264483), Arg198Glu (rs141828689), Gly269Arg (rs552803459), and Asn296Ser (rs552803459) in ABCG5 and Gly512Arg (rs376069170) in the ABCG8 gene have been detected [92].…”
Section: Abcg5 and Abcg8mentioning
confidence: 99%